Master’s Degree Students at Russian Universities: Social Behavior and Quality of Training - S. N. Makarova; S. D. Reznik (Высшее образование в России)
The article analyses the features of students’ social behavior during the period of preparation for training and the period of Master’s study at University. We have chosen third- and fourth-year Bachelor programs students and first- and second-year Master’s programs students from seven regional state universities of Russia as a research object. We have used a specially developed questionnaire. The analysis of the results of complex monitoring of Bachelor and Master’s students made it possible: to estimate the degree of Bachelor students’ awareness of the purpose of master studies and their readiness to make the choice; to define the motives of both groups of students for studying on master’s programs; to estimate financial position of the Russian master’s students. We discuss the mechanisms to improve the quality of Master’s program educaional process at Russian higher education institutions, which will promote more effective functioning of the master’s studies system in Russia. We also offer a complex of scientific and methodological resources providing a general information field for all the participants of educational process aimed at improvement of the quality of master preparation at Universities.